Preparation of polymer electrolytes based on polyurethane elastomer by the swelling method - Fedorov, Nikita Alexandrovich; Uvarov, Nikolai F.; Ulihin, Artem S. (Электрохимическая энергетика)
The search for solvents to prepare polymer electrolytes based on polyurethane elastomer by swelling method was carried out. The greatest swelling was observed in N-methyl-2-pyrrolidone, and the maximum degree of swelling was reached in 24 hours at 25°C. The swelling effect decreased with increasing the salt concentration. The ionic conductivity of the polymer electrolytes reached the maximum of 6–8·10-4 S/cm at 5 wt% of lithium salt. Using the method of galvanostatic cycling it was shown that the electrolyte was reversible by lithium ions and electrochemically stable in the voltage range up to 4.8 V